Profesionalisme Kerja Pustakawan Sebagai Gerakan Moral Dalam Mendukung Kebermanfaatan E-Library - Annisa Susinta; Sri Junandi (Al-Ma'mun, 2022)
This study aims to identify the professionalism of librarians in utilizing the use of information and sharing information to support and develop digital libraries (E-Library). Research methods. This study uses a qualitative method based on rationalism. This study uses an analysis by looking at “morals and character based on rationalism. The data collection is based on literature, observations, and social media sources relevant to this research.” Results and Discussion. The moral movement is the main key to working librarian loyalty in information literacy, supported by the principles of interoperability towards the rules and code of ethics of librarians. Digital library linkage integration, linkage, and collaboration. Integration and linkage between various data formats in large quantities and distributed through global telematics networks. Conclusions and recommendations." Professional librarians must strive to improve their mastery of science and technology as well as information, as well as in the completion and conduct of librarianship tasks, one of which is to support the usefulness of e-libraries. Moral is related to character, philosophy of "kindness" for librarians who can develop the science of "librarianship".